Antipodes : In Search of the Southern Continent - Stallard, Avan Judd (Clayton, Victoria, Australia Monash University Publishing, 2016)
This book is a new history of an ancient geography. It reassesses the evidence for why Europeans believed a massive southern continent existed, and why they advocated for its discovery. When ships were equal to ambitions, explorers set out to find and claim Terra Australis. Antipodes charts these voyages$1 (Bvoyages both through the imagination and across the High Seas$1 (Bin pursuit of the mythical Terra Australis. In doing so, the question is asked: how could so many fail to see the realities they encountered? And how is it a mythical land held the gaze of an era famed for breaking free the shackles of superstition? That Terra Australis did not exist didn$1 (Bt stop explorers pursuing the continent, unwilling to abandon the promise of such a rich and magnificent land till it was stripped of every ounce of value it had ever promised. In the process, the southern continent$1 (Ban imaginary land$1 (Bbecame one of the shaping forces of early modern history. Includes 48 pages of b&w and colour images.s
English
Keywords: Geographical discovery & exploration; History; Antipodes; ancient geography; southern exploration; geographical exploration; exploration by sea; discoveries in geography; discovery of Australia; cartography; historical cartography; imaginative cartography; southern continent; Cosmography; Terra Australis